Role of Histone Deacetylase Inhibitors in Relapsed Refractory Multiple Myeloma: A Focus on Vorinostat and Panobinostat. Issue 12 (December 2015) - Afifi, Salma; Michael, Angela; Azimi, Mahshid; Rodriguez, Mabel; Lendvai, Nikoletta; Landgren, Ola
Abstract : Multiple myeloma is a neoplastic plasma cell disorder that is characterized by clonal proliferation of plasma cells in the bone marrow, monoclonal protein in the blood and/or urine, and associated organ dysfunction and biomarkers. There have been multiple recent advances in the relapsed and refractory setting. Major steps forward include the introduction of proteasome inhibitors (bortezomib and carfilzomib) and immunomodulatory drugs (thalidomide, lenalidomide, and pomalidomide) in various combinations. These drugs have changed the management of multiple myeloma and have extended overall survival in the past decade. Established curative therapy is not yet available for patients diagnosed with multiple myeloma, supporting the development of new treatment targets. Histone deacetylase inhibitors have multiple proposed mechanisms of action in the treatment of multiple myeloma. Both vorinostat and panobinostat have demonstrated some activity against multiple myeloma, and due to the benefits reported with panobinostat, the U.S. Food and Drug Administration has recently approved the drug for the treatment of relapsed and refractory multiple myeloma. In this article, we describe the pharmacology, efficacy, and toxicity profile of vorinostat and panobinostat and their possible place in therapy.